Urgensi Etika Dalam Menjaga Integritas Profesi Akuntansi Manajemen - Fidya Nur Meilia; Mezaluna, Ibtisam; Janibah, Ardina; Misidawati, Dwi Novaria (Ekonosfera: Jurnal Ekonomi, Akuntansi, Manajemen, Bisnis dan Teknik Global, 2025)
This study aims to examine the urgency of implementing ethics in maintaining the integrity of the management accounting profession. The management accounting profession has a strategic role in providing financial and non-financial information for internal company decision making. However, the increasing cases of ethical violations such as financial statement manipulation and asset misuse indicate the importance of enforcing the principles of professional ethics. This study uses a descriptive qualitative method with a literature study approach, which analyzes various literatures to identify the factors causing ethical violations, common forms of violations, and strategies for strengthening professional ethics. The results of the study indicate that ethical violations are caused by weak personal integrity, organizational pressure, lack of internal supervision, and a permissive work culture. Meanwhile, the application of ethical principles such as integrity, objectivity, competence, confidentiality, and professionalism has proven to be an important foundation in maintaining credibility and trust in the profession. Therefore, strengthening ethics through education, a healthy organizational culture, and a strict supervision system are strategic steps to maintain the integrity of the management accounting profession.